EVALUASI KESESUAIAN LAHAN GAMBUT UNTUK PENGEMBANGAN NANAS (Ananas comosus Merr) DI DESA RASAU JAYA II KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Hairi Gunadi; Feira Budiarsyah Arief; Rini Hazriani (Fakultas Pertanian Universitas Tanjungpura, 2013)
ABSTRAC Characteristics of peatlands in the village of Rasau Jaya Jaya II Sub Rasau Kubu Raya district is suitable for cultivation of pineapple (Ananas comosus Merr). Pineapple is plant industry has the opportunity and potential to be developed as a commodity. The purpose of this study was to assess the suitability of land for development in the study sites pineapple plant (Ananas comosus Merr) along with the constraints and repair recommendations. Land suitability evaluation results to the sub-group displays limiting factors in SPT 1 and SPT 2 which indicates a need for land management in an effort to land use. Application of Geographic Information Systems (GIS) spatial information present in the form of maps kesesuaaian land for pineapple crops and area information of each soil map unit. Land evaluation results indicate there are several limiting factors on the thickness and maturity of the SPT 1 and at SPT 2 peat thickness. Land suitability evaluation efforts need to be supported by the provision of management advice among other recommendations for improvement of drainage, liming and fertilizer recommendations. Keywords: Land Suitabbility evaluation, Peat, Pineapple.